1966
DOI: 10.4141/cjps66-005
|View full text |Cite
|
Sign up to set email alerts
|

The Climate, Native Vegetation, and Soils of Some Grasslands at Different Elevations in British Columbia

Abstract: The soils and native vegetation of 28 Outstanding changes in plant species across two phases of the Festuca zone and a high soil"organi"c carbon g.idi"trt through the Black soils appeared to be a result of a high negative mein minimum temperature gradient which accounts for a high P/E ratio gradient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…Based on the predominant A horizon colours, the Carmacks and Kluane pedons are Dark Brown Chernozems, and the Stikine pedon is a Brown Chernozem. Ah horizon organic C concentrations are within the range reported for Brown and Dark Brown Chernozems in the central (Valentine et al 1987) and southern interior (Van Ryswyk et al 1966;Fenger 1982) of British Columbia. For the Carmacks pedon, the Ah1 horizon organic C concentration is comparable with those of grassland A horizons elsewhere in the Carmacks area (Strickland et al 2005).…”
Section: Discussionsupporting
confidence: 52%
“…Based on the predominant A horizon colours, the Carmacks and Kluane pedons are Dark Brown Chernozems, and the Stikine pedon is a Brown Chernozem. Ah horizon organic C concentrations are within the range reported for Brown and Dark Brown Chernozems in the central (Valentine et al 1987) and southern interior (Van Ryswyk et al 1966;Fenger 1982) of British Columbia. For the Carmacks pedon, the Ah1 horizon organic C concentration is comparable with those of grassland A horizons elsewhere in the Carmacks area (Strickland et al 2005).…”
Section: Discussionsupporting
confidence: 52%
“…over a distance of approximately 10 km. Elevation influences precipitation, ranging from 250 mm/year at lower elevations to 350 mm/year at upper elevations, which has established a gradient of plant productivity (van Ryswyk et al 1966 Grasslands in LDB park are grazed by cattle from April to November on a rest and rotation schedule at an Animal Unit Measurement of approximately one cow per hectare. Pastures grazed in the spring one year have been rested the second year, grazed in the fall the third year, and rested the fourth year on an ongoing cycle over the past four decades.…”
Section: Study Areamentioning
confidence: 99%
“…The gradient of moisture effectiveness found across elevations also has an effect on a number of soil physical and chemical properties. Some differences in soil properties with increasing elevation include increased cation exchange capacity (CEC), increased potassium (K), calcium (Ca), and magnesium (Mg), increased organic carbon, decreased C/N ratios, and decreased soil bulk density (Van Ryswyk et al 1966).…”
Section: Physiography Climate and Soilsmentioning
confidence: 99%
“…Other common species include P. Secunda, E. nauseosa, A. frigida (Meidinger and Pojar 1991). Van Ryswyk et al (1966) described these changes in vegetation zones as abrupt, and found that they were related to sharp differences in the ratio of precipitation to temperature.…”
Section: Ecologymentioning
confidence: 99%